Analisis Hubungan Intensitas Praktik Glossolalia dengan Fungsi Kognitif Mahasiswa Sekolah Tinggi Teologi: Pendekatan Kualitatif-Eksploratif - Samuel Elkana; Donalia Reynaldo (Sekolah Tinggi Teologia Kerusso Indonesia, 2026)
This study aims to analyze the relationship between the intensity of glossolalia practice and cognitive functioning among theological college students through a qualitative-exploratory approach. Glossolalia, commonly practiced within charismatic Christian traditions, has generally been examined from theological and phenomenological perspectives, whereas its relationship with cognitive aspects remains relatively underexplored. This study employed in-depth interviews and participant observation involving theological college students who actively engage in glossolalia as part of their regular spiritual practice. The findings indicate that a higher intensity of glossolalia practice is associated with increased self-awareness, improved emotional regulation, and heightened internal focus. These experiences indirectly contribute to several cognitive functions, particularly attention, reflective awareness, and metacognitive reflection. The study also shows that students perceive glossolalia not only as a spiritual expression but also as a practice that supports inner concentration and personal reflection. These findings contribute to interdisciplinary discourse between practical theology and cognitive science by offering insights into how spiritual practices may relate to cognitive processes. Furthermore, this study provides a conceptual foundation for further empirical research using broader samples and measurable cognitive indicators in future investigations.